Steroid-resistant peripheral neuropathy in a child: a rare finding in immunoglobulin a vasculitis - Aydın, Fatma; Kurt, Tuba; Ünlü, Ece; Tekin, Zahide Ekici; Çelikel, Elif; Acar, Banu Çelikel (The Turkish Journal of Pediatrics, 2022)
Background. Immunoglobulin A vasculitis (IgAV; Henoch-Schönlein purpura) is the most common vasculitis of childhood, affecting the small vessels with systemic involvement, especially the skin, joints, gastrointestinal system and kidneys. Peripheral neuropathy is very rare. Herein, we present a patient who was diagnosed as IgAV and developed refractory peripheral neuropathy in the course of disease. Case. An 11-year-old boy was admitted to our clinic with pain and swelling in both ankles and symmetric palpable purpura extending from the knees to the dorsum of his feet. IgAV diagnosis was established and outpatient follow-up was started. On the 18th day of follow-up, he was admitted with widespread palpable purpura, myalgia and edema in the lower extremity, abdominal pain and left scrotal swelling. Intravenous prednisolone 2 mg/kg/day was started, all his symptoms improved and edema was resolved, but on the third day of the prednisolone therapy, the patient suffered from numbness in the left foot. Electromyoneurography showed moderate to severe axonal degeneration of the left tibial nerve. The symptoms of patient didn`t improve with bolus methylprednisolone and intravenous immunoglobulin therapy. All of the patient`s neurological complaints and signs regressed significantly within one week after bolus cyclophosphamide therapy. His oral prednisolone was gradually tapered and stopped at the end of the third month. After a follow-up period of six months, the patient had no complaints. Conclusion. Peripheral neuropathy is a rare complication of IgAV and occasionally it could be severe. Cyclophosphamide therapy should be kept in mind in patients with refractory neuropathy due to IgAV.
Keywords: IgA vasculitis; cyclophosphamide; pediatric patient; peripheral neuropathy; steroid